Detection of neurogenic detrusor contractions from the activity of the external anal sphincter in cat and human - Wenzel, Brian J.; Boggs, Joseph W.; Gustafson, Kenneth J.; Creasey, Graham H.; Grill, Warren M. (Neurourology and urodynamics, 2006)
Aims Individuals with spinal cord injury or neurological disorders may develop bladder contractions at low volumes (neurogenic detrusor overactivity), which can lead to significant health problems. Present devices can inhibit unwanted contractions through continuous electrical stimulation of sensory nerves, but do not enable conditional stimulation only at the onset of bladder contractions. The objectives of this study were to determine the relationship between the electrical activity of external anal sphincter (EAS) and bladder pressure during neurogenic detrusor contractions and to determine whether EAS activity could be used to detect the onset of bladder contractions. Methods Bladder pressure and EAS electromyogram (EMG) were recorded in nine adult male cats. Retrospective clinical data consisting of bladder pressure and EAS EMG from 41 spinal cord injured individuals with neurogenic detrusor overactivity were analyzed. A CUSUM algorithm was used to detect the onset of bladder contractions from the EAS EMG. Results EAS EMG activity increased at the onset of bladder contractions in six cats (dyssynergic) and decreased (synergic) in three cats. The onset of bladder contractions was detected within 3 sec of the start of the contraction for both the synergic and dyssynergic data sets. The onset of bladder contractions was detected within 1 sec of the start of the bladder contraction for both synergic and dyssynergic human subjects. Conclusions Recordings of the EAS EMG can be used to detect robustly the onset of neurogenic detrusor contractions. The EAS EMG is a suitable signal to control closed‐loop inhibitory electrical stimulation to maintain urinary continence. Neurourol. Urdynam. © 2005 Wiley‐Liss, Inc.